Frequency and power shaving controller for grid-connected vanadium redox flow batteries for improved energy storage systems - Qazi, Sajid Hussain; Bozalakov, Dimitar V.; Vandevelde, Lieven (Frontiers in Energy Research, 2024)
In this research the performance of Vanadium Redox Flow Batteries (VRFBs) in grid-connected energy storage systems centering on frequency and power sharing using voltage source inverter was evaluated. VRFBs are increasingly promising due to their scalability and long lifespan. We explore the impact of voltage source inverter on frequency of the power supply when there is change in load and power sharing between grid and VRFB through MATLAB simulations. The test system demonstrate a storage system at a 11kV substation and considers a load profile commencing from a residential and commercial consumers. The outcome of this study reveals that VRFB provides required power to maintain load demand. Due to fast response time VRFB also regulates the frequency efficiently during the change in load demand and maintaining current THDs. This research confirms the design and operation of VRFB-based energy storage systems, contributing to resilient grid infrastructure and reliable power distribution system.